2009
DOI: 10.1109/tdei.2009.5293959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electric partial discharges on the rheological and chemical properties of polymers used in HV composite insulators after railway service

Abstract: The origin and the consequences of the electric failure of in-service composite hollow insulators used in railway transportation were investigated. Direct electrical measurements made it possible the detection of partial discharges (PD) and UV emissions allowed of identifying the location of the PD at the interface between metal braids and a silicone liner. To investigate the effects of the damaging PD activity, physicochemical properties of the different polymers were investigated and compared to new samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In other words, porcelain has a weak bonding force between its molecules, unlike heat tempered glass and silicone (silicone has a strong bonding force between its molecules made from oxygen and silicon). Thus, this chemical structure plays a main role in the electrical and dielectric properties of these materials [25].…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…In other words, porcelain has a weak bonding force between its molecules, unlike heat tempered glass and silicone (silicone has a strong bonding force between its molecules made from oxygen and silicon). Thus, this chemical structure plays a main role in the electrical and dielectric properties of these materials [25].…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…In fact, during surface electrical discharge due to a significant increase in temperature, both degradation of the matrix polymer and dehydration of the ATH-like filler present in the compound can happen. 44,8992 Therefore, it may be concluded that the second stage decomposition temperature measured through TGA for a housing material is related to its service life.…”
Section: Resultsmentioning
confidence: 99%
“…However, the housing material may be exposed to a much higher temperature well beyond 170 °C, the highest aging temperature for a very short duration during electrical discharges. 44,8992…”
Section: Resultsmentioning
confidence: 99%
“…This could be the main reason that leads to tracking due to its lowest activation energy. Furthermore, a reduction in the percentage of C‐H and pyrolysis of sulphuric components (‐S) are likely to facilitate the ignition of a conducting path and gas by‐products such as SO 2 and H 2 S [26]. As concerns HDPE, its resistance to tracking in salt fog is better than that in clean fog probably due to a higher leakage current magnitude that dries quickly the moisturised surface and inhibits FOV arcs.…”
Section: Discussionmentioning
confidence: 99%